Understanding student motivation towards achieving goals among college students: an exploratory research - Nilda Wines Balsicas; Eddie Rima Cabrera; Elgien Candelaria Padohinog; Freddie Bulauan (Institute of Advanced Engineering and Science, 2026)
Motivation could be the greatest currency to succeed in a student’s academic life. This study analyzed academic motivation after students were affected by the pandemic or after their two-year hiatus from active academic face-to-face activities. Moreover, this research examined whether students have influenced academic motivation in terms of gender and degree of program. Using a descriptive-sequential research design, 652 college students at St. Dominic College of Asia, Cavite, Philippines, took part in this study. A survey questionnaire adapted from the academic motivation scale (AMS-C 28) college version was used to determine the level of academic motivation of students. Open-ended questions were provided to the students relating to what motivates them to study and to which students are motivated through techniques during online learning. Findings revealed that the degree of program has a positive effect on student motivation, whereas gender does not significantly associate with motivation. Students showed appreciation for a greater convenience to study because of the technology; however, lack of interaction makes it more challenging for some. Helping students as teachers to keep track of their tasks can make them become great learners and succeed with confidence and determination through their personal and scholarly lives.